Chinese education and Chinese identity in Malaysia - Lee, Yok Fee (Department of History Education, University of Education Indonesia, 2009)
In general, research and discourse on the concept of identity has been naturally evolved as the changes of social structures in social processes, such as industrial affairs, modernization, and globalization, are expanding as well. The concept of identity, meanwhile, has also changed by following the development of social thoughts, i.e. the formation and change in the philosophy of knowledge paradigm, such as the development of structural theoretical perspective to post-structural and post-modernism (Bendle, 2002; Lee, 2007).